Apresentação do Seminário em homenagem ao centenário de nascimento do Dr. Herbert Moritz Caro - Gutfreind, Ieda (Contingentia, 2008)
Introduction of the seminar dedicated to Herbert Caro, held on the 16th of October 2006 at the Goethe-Institute Porto Alegre, Brazil.